Factors secreted from dental pulp stem cells show multifaceted benefits for treating experimental temporomandibular joint osteoarthritis. Issue 6 (June 2020) - Ogasawara, N.; Kano, F.; Hashimoto, N.; Mori, H.; Liu, Y.; Xia, L.; Sakamaki, T.; Hibi, H.; Iwamoto, T.; Tanaka, E.; Yamamoto, A.
Summary: Objective: Temporomandibular joint osteoarthritis (TMJOA) is a degenerative disease characterized by progressive cartilage degeneration, abnormal bone remodeling, and chronic pain. In this study, we aimed to investigate effective therapies to reverse or suppress TMJOA progression. Design: To this end, we performed intravenous administration of serum free conditioned media from human exfoliated deciduous teeth stem cells (SHED-CM) into a mechanical-stress induced murine TMJOA model. Results: SHED-CM administration markedly suppressed temporal muscle inflammation, and improved bone integrity and surface smoothness of the destroyed condylar cartilage. Moreover, SHED-CM treatment decreased the number of IL-1β, iNOS, and MMP-13 expressing chondrocytes, whereas it specifically increased PCNA-positive cells in the multipotent polymorphic cell layer. Notably, the numbers of TdT-mediated dUTP nick end labeling (TUNEL)-positive apoptotic chondrocytes in the SHED-CM treated condyles were significantly lower than in those treated with DMEM, whereas the proteoglycan positive area was restored to a level similar to that of the sham treated group, demonstrating that SHED-CM treatment regenerated the mechanical-stress injured condylar cartilage and subchondral bone. Secretome analysis revealed that SHED-CM contained multiple therapeutic factors that act in osteochondral regeneration. Conclusions: Our data demonstrated that SHED-CM treatment promoted the regeneration and repair of mechanical-stress induced mouse TMJOA. Our observations suggest that SHED-CM has potential to be a potent tissue-regenerating therapeutic agent for patients with severe TMJOA.